2020
DOI: 10.25092/baunfbed.742631
|View full text |Cite
|
Sign up to set email alerts
|

Boru profilli gemi jeneratör kaidelerinin titreşim açısından analitik ve sayısal analizi

Abstract: Gemiler, çok büyük ve karmaşık yapılar olduklarından bünyelerinde titreşim kaynağı sayılabilecek bir çok eleman bulundurmaktadırlar. Bu çalışmada, gemi üzerinde yerel titreşimlere neden olan gemi jeneratör setleri için titreşim sönümleyici görevi gören ve farklı açılarda tasarlanmış boru profillerden oluşan tabla tipi 11 farklı kaide tasarımı üzerinde durulmuştur. Bu yapılar hem analitik hem de sonlu eleman yöntemiyle incelenmiştir. Çalışma, genel olarak, gemi jeneratör seti ve kaidelerinin katı modelleme yazı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…They concluded that Hardware-in-the-Loop testing is a suitable methodology for testing and validating complex control systems. Yücel et al (2020) performed the analytical and numerical vibration analysis on the generator set foundations with pipe profiles on ship. They determined the optimal design of the generator base, which acts as a vibration damper.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that Hardware-in-the-Loop testing is a suitable methodology for testing and validating complex control systems. Yücel et al (2020) performed the analytical and numerical vibration analysis on the generator set foundations with pipe profiles on ship. They determined the optimal design of the generator base, which acts as a vibration damper.…”
Section: Introductionmentioning
confidence: 99%